The adjustments of home interiors for fitness during COVID-19 lockdowns and the new normal - Picazo, Kaye Patricia M. (College of Home Economics, University of the Philippines Diliman, 2023)
This research identified the specific areas of the residential interiors which were utilized for exercising, discussed the spatial adjustments made in home interior spaces during the COVID-19 pandemic lockdowns to accommodate exercising at home, and described the experience of exercising at home in the new normal after making exercise-related adjustments to the space. This study is a qualitative descriptive research where a non-probability purposive sampling method was used to gather a total of 6 respondents, wherein 3 lived in single detached dwellings and 3 lived in condominium units in Metro Manila, who have been regularly exercising at home and have made spatial adjustments to their initial exercising space to accommodate their exercise routine during the COVID-19 lockdowns. The data gathering methods include photo documentation, semi-structured interview, and production of approximate floor plans. The collected photos and produced approximate floor plans were individually presented whilst data from the interviews were then summarized or ranked into tables. Through thematic analysis of data supported by the Design Narrative Theory (Ganoe, 1999) and a look into the Indoor Environment Quality (IEQ) (Dang et al., 2021) factor that is layout, it was found that the bedroom is the most utilized area for exercising. The main spatial adjustments made to accommodate exercising at home is the relocation of furniture pieces within the room. The experience of exercising at home after adjustments were made is enhanced through the personalization of the space and the use of the most important aspects of space–which was found to be the new arrangement of furniture. Home interiors for fitness was observed to be significant to the exercising experience as all respondents have provided distinctly personal meanings to their spaces that are unique for each individual. It is recommended for future research to explore other design criteria from the Design Narrative Theory and other IEQ factors when observing adjustments made to exercise spaces.